Local bank competition and small business lending after the onset of the financial crisis - Sääskilahti, Jaakko (Journal of Banking & Finance, 2016)
This paper examines whether the effects of the financial crisis on the volumes and prices of small business loans depended on the pre-crisis local competitive environment. To address this question, I employ a unique data set on Finnish cooperative banks. I find that the monthly volumes of new business loans decreased and the average loan margins increased after the onset of the crisis. The decrease in volumes and the increase in margins were greater in local banking markets that were more competitive before the crisis. The results for the loan margins are more robust than those obtained for the volumes. Auxiliary analyses suggest that the greater effects in the more competitive markets are due to competition leveling therein more after the onset of the crisis.